ANTOLOGI HADIS TARBAWI PESAN-PESAN NABI TERKAIT PENDIDIKAN SEBAGAI LANDASAN DALAM MENGHADAPI TANTANGAN ZAMAN MODERN - Kurjum, Mohammad; Qurratina, Noor Shania (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2025)
This research aims to analyze the messages in the hadith of the Prophet SAW. which can be used as a basis for facing the challenges of the modern era. This research uses a descriptive-qualitative research method with a hadith study approach. Data collection uses literature study techniques with content analysis techniques. The results of this research are: There are several hadiths of the Prophet that are relevant to facing educational challenges in the modern era, including those that include the development of students' ethics, integrity, creativity and mental resilience. Moral values such as good morals, the importance of knowledge, the role of the family in education, and the development of 21st century skills are reflected in the Prophet's teachings, which also emphasize patience and problem solving as part of the learning process. These hadiths provide guidelines that can be applied in today's education to form a generation that is not only intellectually intelligent, but also morally and emotionally strong.